Educação ambiental dialógico-crítica no Pantanal de Mato Grosso : a voz e o silêncio das pescadoras e dos pescadores tradicionais - Souza, Silvano Carmo de (2017)
The research of critical-dialogical environmental education was developed in the municipality of Caceres, Pantanal of Mato Grosso. It is work done by many hands, the results of many voices meeting. Fruit of the interaction of workers who have their lives interwoven by the uneasy rhythm of the waters of the Pantanal rivers of Mato Grosso. During approximately 2 years we dialogue with traditional fishermen linked to two entities representing the category: Colony Z-2 and the Association of fishermen of Caceres – Appec. Before entities were affiliated, these people and/or their families had traditionally developed, for decades, fishing for subsistence. Our main objective was to contextualize the artisanal fishing activity in the municipality of Caceres, starting with an egalitarian dialogue with fishermen, in order to simultaneously promote processes of critical dialogic formation with them, especially from and regarding their contexts. To do so, we launched the freirean and haberman theoretical and methodological referential, densely consubstantiated in the critical communicative methodology. In this dialogical diagnostic, analytical revealing and propositional transformative process, we discuss three themes, considered by them and by them as the main ones: a) the practice of artisanal professional fishing; b) participation in the political actions of Colony Z-2 and Appec and in the processes of formulation of public fisheries policies, and c) conservation of fish biodiversity. The results, analyzes and developments of this research are listed in part two of this thesis. There are five articles in which we seek, in addition to retaking in each of them the theoretical and methodological framework that underlies this work, we also discuss the reflections we carry out dialogically with 83 professional fishermen. In the four articles are listed the motives of the lucid voice and the deafening silence that drove our movements during the time we were together. To a large extent, we have identified a growing disposition within the fishing communities for the freiran dialogue. Despite all the violence to which these people have already been and are submitted, the disposition to face the processes of spoliation of rights persists keenly. Therefore, the importance of environmental education research based on values, practices and critical dialogic concepts, since these potentialize the coordination of actions with a view to overcoming the processes of oppression, potentialization as historical subjects, which are also able to read his world and seek his transformation.